Hannah Arendt and Augustine of Hippo : On the Pleasure of and Desire for Evil - Calcagno, Antonio (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2010)
Hannah Arendt wrote two volumes on thinking and willing in The Life of the Mind, but due to her untimely death her work devoted to judgement, especially political judgement, was never completed. We do, however, have a significant amount of writings on this theme as evidenced by her lectures on Kant’s Third Critique. Judgement and thinking are critical in order to prevent what Arendt calls the “banality of evil”. Drawing on Augustine and Arendt’s work on Augustine, this paper seeks to argue that another form of serious evil has its root in what Augustine calls the libido habendi and the libido dominandi, the desire or drive to dominate and possess. It will be argued that Arendt’s solution to the problem of evil as banal can also be applied to the very human desire and pleasure to cause or inflict evil.